Characterization of Si3N4 Metal-Insulator-Metal (MIM) Capacitors for Monolithic Microwave Integrated Circuits (MMIC) Applications - Lee Hock Guan; Osman, M.N.; Dolah, A.; Rahim, A.I.A.; Yahya, M.R.; Mat, A.F.A. (2006 IEEE International Conference on Semiconductor Electronics, 2006)
The fabrication of the MIM capacitors is illustrated in the paper. The effective capacitor areas are designed at 60 × 60, 240 × 240 and 380 × 380 μm 2 . From the s-parameter measurements, the fabricated capacitors showed capacitive capability up to frequency of 40GHz. Strong parasitic effect was observed at low frequency while attenuation effect was observed at high frequency.